REALITAS SOSIAL ANAK YATIM DI KOTA PADANG DALAM PERSPEKTIF PEMBERDAYAAN MASYARAKAT - Mardan Mahmuda (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
The economic and religious condition of orphans in the coastal and confine areas of Padang City are being concerned. While the attention of Moslem to empower their economic and religiousness is still lacked. This research focused on the disclosure of realities in poverty and religiousness of orphans in the coastal and confine areas of Padang City, then it would be analyzed based on the perspective of community empowerment by using descriptive qualitative method. The results of this study show that: (1) The reality of poverty of orphans in the coastal and confine areas of Padang City is very worrying and requires special empowerment. The poverty can be observed from the condition of house that is suffered a lot of damage and the difficulty of the expense of basic foods they encountered. (2) The reality of religiousness of orphans is also being concerned. The religious problem is considered from the implementation of prayers and reading Qur'an that they have not done best yet. Meanwhile, The attention had been given by the board of mosque and mushalla was only a bit advice when distribute of compensation money. This research is expected to be a contribution for da’wah practitioners, empowerment agencies, mosque and mushalla administrators, religious institutions and other social institutions in Padang City and throughout Indonesia for the welfare of orphans through empowerment activities.